Identity Diffusion and Extremist Attitudes in Adolescence - Isenhardt, Anna; Kamenowski, Maria; Manzoni, Patrik; Haymoz, Sandrine; Jacot, Cédric; Baier, Dirk (Frontiers in Psychology, 2021)
Various theoretical approaches assume that identity diffusion is an influencing factor of extremism. However, there are hardly any empirical tests on this relationship. Based on a nationwide survey of 8,317 young people in Switzerland, the study analyses whether identity diffusion is associated with right-wing extremist, left-wing extremist, and Islamist extremist attitudes. In addition, the study tests whether identity diffusion mediates the influence of family and school-related variables on extremist attitudes. The results show that identity diffusion primarily increases approval of left-wing extremist and Islamist extremist attitudes. Furthermore, identity diffusion mediates to a small extent the influence of parenting on extremist attitudes.